Microbial production of extracellular polysaccharides from biomass sources - (:unkn) unknown (Springer International Publishing, 2015)
The interest in bio-based polymers, especially extracellular polysaccharides (EPSs), has increased considerably in recent years due to their useful physicochemical and rheological properties and diverse functionality. Microbial polysaccharides have many commercial applications in different industrial sectors like chemical, food, petroleum, health, and bionanotechnology. Although microbial EPS production processes are regarded as environmentally friendly and in full compliance with the biorefinery concept, EPSs constitute only a minor fraction of the current polymer market due to their cost-intensive production and recovery. For that reason, much effort has been spent to the development of cost-effective production processes by using cheaper fermentation substrates such as low-cost biomass resources. These resources are generally either in liquid form like syrups, molasses, juices, cheese whey, and olive mill wastewater or solid-like lignocellulosic biomass and pomaces. In this chapter, after a brief description of microbial polysaccharides, submerged and solid-state fermentation processes utilizing cheap biomass resources are discussed with a special focus on the microbial production of EPSs with high market value. © Springer International Publishing Switzerland 2015.
Keywords: Biomass resources; EPS; Fermentation; Microbial exopolysaccharides; Polysaccharides